Revitalizing Ancient Balinese Yoga: A Strategic Framework for Sustainable Spiritual Tourism Development Anchored in Divine Transcendence - Ni Kadek Surpi; I Gusti Ngurah Sudiana; I Ketut Arta Widana; I Ketut Sudharma Putra (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
This study examines the revitalization of ancient Balinese yoga as a sustainable spiritual tourism product rooted in the concept of divine transcendence. Ancient Balinese yoga, which has preserved 14 lineages of world yoga since 541 AD, is a unique cultural heritage that has not been widely utilized in modern tourism. Using a mixed-methods approach that involves qualitative interviews with key stakeholders, focus group discussions, and a quantitative survey of 150 potential tourists, this study formulates a strategic framework for developing this traditional form of yoga into an authentic and sustainable spiritual tourism product. The study's results demonstrate significant potential for revitalizing ancient Balinese yoga, focusing on three key dimensions: authenticity preservation, marketability, and local community engagement. Four strategic tourism packages are proposed: cultural performances, training programs, retreat packages, and instructor courses. This study highlights key success factors such as instructor development, infrastructure needs, and marketing strategies that maintain cultural integrity while meeting modern tourism demands.